VARIOUS CORRECTIVE FEEDBACK TYPES IN COLLABORATIVE VS. INDIVIDUAL WRITING CONDITIONS - Soleimani, Maryam; Modirkhamene, Sima (Institute of Advanced Engineering and Science, 2020)
One of the important issues in EFL instruction is the idea of eliminating students? linguistic errors through providing corrective feedback (CF). Accordingly, this study investigated the effect of various CF types (i.e., comprehensive, selective, and no feedback) on advanced EFL learners? writing in different writing conditions (i.e., individual & collaborative). 132 EFL advanced learners aged from 14-20 were considered as the main participants. Learners were divided into 6 groups (i.e., three individual and three collaborative writing conditions). Furthermore, each writing condition included three groups with selective, comprehensive and no correction orientations. Data collection tools and procedures encompassed an institutionalized Placement Test, pre-test, and post-test. The treatment that lasted for nine sessions was followed by a post-test. Data was submitted to a series of ANOVA tests with follow up pair-wise comparisons and independent-samples t-tests. Findings indicated that: (1) CF, especially selective one, was more effective in enhancing learners? writing accuracy, and (2) members of the collaborative writing groups outperformed those in the individual ones in terms of their writing accuracy development. The theoretical and practical implications are discussed in relation to enhancing writing accuracy of the learners.